ASUHAN KEPERAWATAN KANKER NASOFARING DENGAN FOKUS STUDI PENATALAKSANAAN NYERI DI RSUD TIDAR KOTA MAGELANG - Sri Rahayu (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
Cancer / nasopharyngeal carcinoma (NPC) is a malignant cancer in the head and neck. This cancer is located in the nasopharynx, behind the nose. NPC including five large malignant tumors. Ebstein Barr is one of the triggers of this carcinoma. Most NPC patients come to the clinic for treatment at an advanced stage. The purpose of writing is to discuss and examine the application of nursing care with a focus on pain studies on clients with nasopharyngeal cancer. The method used by the writer is descriptive by managing one client who has nasopharyngeal cancer. The results of the study were obtained as long as 2x24 hours of nursing care was provided, the pain problem was resolved in accordance with the established criteria with the results of the implementation carried out in accordance with the client's developmental response. During the evaluation of nursing care that has been given for 2 consecutive days there is a nursing problem that pain can be resolved. Keywords: Nasopharyngeal Cancer, Pain, Nursing Care